Central and Eastern European agriculture in an expanding European Union [ - Banse, M. [ (Martin)]; Tangermann, Stefan (CABI, 2000)
This book reports on results achieved in a research project that dealt with agriculture and the food industry in Central and Eastern European Countries (CEEC). It examines the current economic conditions and the changes that are taking place and yet mus occur, in the process of preparing for accession to the European Union. The project was structured in six tasks, ranging from methods to analyse the economic situation in agriculture, through an analysis of productivity in CEEC agriculture, a study of economic transfers along the food chain, research into market developments under policy adjustment to the Common Agricultural Policy (CAP), and an analysis of macroeconomic implications of accession, all the way to an investigation of agricultural policy developments in CEECs.